Young children's differential use of power during family conflict: A longitudinal study. Issue 1 (13th July 2021) - Della Porta, Sandra; Persram, Ryan J.; Howe, Nina; Ross, Hildy S.
Abstract: This study identified longitudinal and birth order differences in young children's use of power over a 2‐year period; the sample included 2‐ and 4‐year‐old (T1) and 4‐ and 6‐year‐old (T2) siblings ( n  = 39). Power was investigated via its use (i.e., actions) and effectiveness (i.e., successful actions) during naturally occurring polyadic family conflicts at home involving three or more family members (two children and at least one parent or two parents and at least one child). Observations were transcribed and sequences of polyadic family conflict (T1 n  = 780; T2 n  = 210) were identified and coded for power (coercive, reward, legitimate, simple, information) and conflict resolution (win‐lose, compromise, no resolution); win‐lose resolution was used as an indicator of power effectiveness, by isolating winning cases for the analyses. Differences in power use and effectiveness were revealed across both time points and birth order, namely between 4‐year‐old older siblings at T1 and 4‐year‐old younger siblings at T2. Results provide insight into young children's power behavior within the family context.